Prime riflessioni a margine della legge n. 219/17 (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
Law 219/17 regulates, for general rules and principles, the therapeutic relationship between doctor and patient with specific regard to: informed consent in health, advance treatment declarations and advanced care planning. In implementation of the principles contained in the articles 2,13, 32 of the Constitution and 1, 2, 3 of the EU Charter, defines the perimeter of the therapeutic self-determination of the person by regulating contents, forms and limits of consent to health treatment (with general application), of advance directives focusing on the value binding of the will expressed “now by then” of the agreement on the therapeutic program agreed with the doctor and on the figure of the trustee.
Keywords: Dignity; therapeutic self-determination; informed consent; advance directives; shared care planning